1980
DOI: 10.1136/adc.55.8.589
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system involvement in progressive muscular dystrophy.

Abstract: SUMMARY Several abnormalities in the central nervous system were shown in patients with progressive muscular dystrophy using computerised tomography (CT) scans, electroencephalograms, psychometry, and ophthalmological methods. In congenital muscular dystrophy, the most characteristic finding in the CT scan was a low density area in the white matter, seen in 14 (56%) out of 25 cases. In Duchenne dystrophy, slight cerebral atrophy was observed in 20 (67%) out of 30 cases. It was interesting that in the case of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
6

Year Published

1985
1985
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(50 citation statements)
references
References 12 publications
1
43
0
6
Order By: Relevance
“…Yoshioka et al studied 30 DMD patients and found slight cortical atrophy in 67% of them, slight ventricular dilation (i.e., enlargement of inter-hemispheric cisterns and sulci of 3-5 mm) in 60%, and cortical atrophy in 30%, although clear signs of atrophy were only observed in older and more physically disabled patients (30). However the brain autopsy results, and more recently the brain imaging results, on DMD patients have not been consistent (31).…”
Section: Discussionmentioning
confidence: 99%
“…Yoshioka et al studied 30 DMD patients and found slight cortical atrophy in 67% of them, slight ventricular dilation (i.e., enlargement of inter-hemispheric cisterns and sulci of 3-5 mm) in 60%, and cortical atrophy in 30%, although clear signs of atrophy were only observed in older and more physically disabled patients (30). However the brain autopsy results, and more recently the brain imaging results, on DMD patients have not been consistent (31).…”
Section: Discussionmentioning
confidence: 99%
“…On CT scan, brains of boys with DMD show mild cerebral atrophy (Echenne et al, 1998;Septien et al, 1991;Yoshioka et al, 1980). Abnormal EEGs have been recorded in some, but not all patients tested (Kozicka et al, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…A rupture in the link among DGC proteins occur in the dystrophinopathies (DMDuchenne/Becker), resulting in sarcolemma instability and secondary lesion from muscle contraction 11 . A wide range of abnormalities have been found in 30 cases of DMD patients' brains assessed by Yoshioka 12 : subtle brain atrophy, mild dilated ventriculum and cortical atrophy in and others 13,9 . In another study, an increased incidence of neuronal loss and gliosis, as well as, abnormal dendritic branching and arborization of cortical piramidal neuron was found 14 .…”
mentioning
confidence: 99%